Nevin Halici: Nevin Halici’s Turkish Cookbook - I., P.J.F. (Petits Propos Culinaires, 1990)
Nevin Halici: Nevin Halici’s Turkish Cookbook: Dorling Kindersley, London 1989: 176 pp, introductory essay, recipe, glossary, index and bibliography, colour photographs, £14.95.